Obstructive sleep apnoea and hypoventilation in an adult with congenital myasthenic syndrome. (14th November 2018) - Younas, Haris; Roda, Ricardo; Jun, Jonathan
Abstract : In this case report, we describe an adult male with congenital myasthenic syndrome due to mutations in muscle-specific receptor tyrosine kinase ( MuSK, c.79+2 T>G; IVS1 +2 T>G, c.2368 G>A, Val790Met) presenting with sleep apnoea and hypercapnic respiratory failure. In the intensive care unit, he required intubation followed by tracheostomy which resolved obstructive sleep apnoea. Later, due to persistent sleep-associated hypoventilation, he required nocturnal mechanical ventilation. His case illustrates how respiratory muscle weakness due to mutations in MuSK can lead to various forms of sleep disordered breathing.